Decoding and reprogramming of the biosynthetic networks of mushroom-derived bioactive type II ganoderic acids in yeast - Qin Wang; Ye Li; Shunhan Zhang; Wei Yuan; Zeqian Du; Ting Shi; Zhao Chang; Xingye Zhai; Yinhua Lu; Meng Wang; Juan Guo; Jian-Jiang Zhong; et al. (Cell Discovery)
Abstract Mushroom’s specialized secondary metabolites possess important pharmacological activities, but their biosynthetic pathway elucidation is extremely challenging, not to mention reprogramming of their biosynthetic networks to target metabolites. By taking Ganoderma lucidum, a famous traditional medicinal mushroom, as a lead example, here we decoded the biosynthetic networks of type II ganoderic acids (TIIGAs), a group of its main bioactive metabolites by studying the coordinated gene expression in G. lucidum, identifying endogenous or heterologous enzymes capable of C22 hydroxylation, configuration conversion of C3 hydroxyl group, and acetylation on C3, C15 and C22 hydroxyl groups. Notably, we revealed the catalytic mechanism of the C22 hydroxylase CYP512W6, and an unexpected bifunctional acetyltransferase GlAT that is required to transfer acetyl groups to C15 and C22. Using a fluorescence-guided integration method, we achieved efficient biosynthesis of significant TIIGAs applicable to industrial fermentation. After introducing all the identified enzymes to baker’s yeast, we observed that biosynthesis of downstream TIIGAs was severely impeded, and dredged the metabolic block by temporally regulating the expression of acetyltransferases. By reprogramming of the biosynthetic networks of TIIGAs, we were able to produce over 30 TIIGAs, exhibiting 1–4 orders of magnitude higher titers or efficiencies than those from farmed mushrooms. The work enables the access to valuable TIIGAs, facilitates their widespread application, and sheds light on research of other mushroom products.